An efficient method for reduction of nitroaromatic compounds to the corresponding aromatic amines with NH2NH2·H2O catalysed by H2O2-treated activated carbon. (1st September 2017) - Jiang, Yuqin; Suo, Huajun; Zhang, Dandan; Li, Xiyong; Sun, Yamin; Ren, Baoqi; Zhang, Weiwei; Xu, Guiqing
An efficient and green protocol for the reduction of nitroaromatic compounds to the corresponding amines has been developed. The reduction catalyst system includes NH2NH2·H2O and H2O2-treated activated carbon. Without adding additional metals, the H2O2-treated activated carbon could be reused for many cycles without decreasing catalytic efficiency. The aromatic amines could be obtained in good to excellent yields.